Romanian health system strategic directions for the next decade (Italian Journal of Public Health, 2009)
Background: The exceptional changes in the Romanian society after 1989 have strongly influenced thereforms of the health system.Methods: Several tools were used for this health policy review: finding the evidence to prove that there areimportant public health problems in Romania, as well as reviewing the existing legislation and policy papersrelated to health system, stakeholder analysis, meetings and working groups with key players from the healthsector.Results: Health indicators for Romania are some of the poorest in the WHO European region, not only at EUlevel. A mix of specific indicators for developed countries (e.g. high mortality by cardiovascular diseases,increasing incidence of cancer) and specific indicators for developing countries (e.g. re-emergence of somecommunicable diseases, like TB) can be noticed. Unfavourable comparisons also exist for the indicatorsdescribing the performance of the health system: poor access to basic health services especially in rural area,inadequate human resources management, lack of integration of the health services in order to assure thecontinuity of care, poor health information management, and reduced intersectoral cooperation. Six majorintervention areas have been identified by the Presidential Health Commission set up in 2008, in order toaddress the dysfunctions of the health system: Health system financing, Health system organization, Drugpolicy, Primary care, Hospital services and Human resources. In order to address them, 29 specificrecommendations were made.Conclusions: If the declared intentions of the new minister of health are implemented in line with theproposed presidential strategy, then coherency might finally have a chance to drive the process forward.
Keywords: health systems; health policy; right for health; health care reform; health care; stewardship